Material pre-straining effects on fatigue and fracture structure behaviour of offshore wind monopile structures. - Anandavijayan, Satya Gayathri (Cranfield University, 2021)
An important issue to be considered in the structural integrity assessment of offshore wind monopile structures is the influence of material pre-straining on the fracture toughnessnd fatigue crack initiation and growth behaviour of the material. Material pre-straining can be introduced into monopile cans during the three-roll bending fabrication process. Literature has shown that in certain steels, this pre-straining effect can affect the behaviour of the material, causing it to behave differently to the parent material. A finite element model has been developed to predict the level of plastic strain present in the material after undergoing the three-roll bending process, with a parametric study conducted to determine the effects of fabrication and geometry factors on plastic strain, which may potentially aid fabricators to control the behaviour of the material when in operation. Thus, the main aim of this project is to investigate the effects of material pre-conditioning on the mechanical response, fatigue, and fracture behaviour of an offshore structural steel. S355 steel which is widely used in offshore wind industry for foundation structures such as monopiles has been used in the experimental test programme involving specimens pre-tensioned to 0%, 5% and 10% to investigate the potentially beneficial or detrimental effects. In addition to this, an experimental study on the effect of fatigue damage on the mechanical properties of S355, across varying levels of pre-straining, has been conducted. The results from this study have been employed in the remaining life analysis of monopile structures, such as failure assessment diagrams, to determine appropriate inspection intervals and recommendations necessary to avoid catastrophic failure.